The Development and Implementation of Islamic Legal Products in Indonesia - Rahmatullah R; Abd. Rahman R; Rahmatiah Hi (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study examines Islamic legal products and their implementation in Indonesia within the framework of integrating Sharia values with the national legal system. Islamic legal products are the result of istinba? al-a?kam derived from primary sources such as the Qur’an, Hadith, ijma, and qiyas, which are then applied across various aspects of life. In Indonesia, their implementation is reflected in regulations such as the Compilation of Islamic Law (KHI), the Islamic Banking Law, the Zakat Law, and the Waqf Law, as well as in institutions such as the Religious Courts, BAZNAS, and BWI. This study shows that the implementation of Islamic law takes place through three main channels: substantive law, formal law, and social law. Although significant progress has been made, the application of Islamic law still faces challenges in the form of legal pluralism, differences among schools of thought, and limitations in human resources. Therefore, strengthening regulations, improving the competence of legal practitioners, and promoting interdisciplinary research are necessary to ensure that the values of justice and public welfare (ma?la?ah) in Islam are more deeply internalized within the national legal system.